Cultural politics of hygiene in India, 1890-1940 : contagions of feeling - Prasad, Srirupa, 1971- (Cambridge imperial and post-colonial studies series., 2015)
"Can there be an affective history of hygiene? Is it possible to read into the narrative of modern hygiene active and animated tropes of emotion, affect, and feeling? New microbes, novel pandemics, and their global movements that have forcefully reinstated the efficacy of hygiene have also reinvigorated global academic interest in the genealogies of hygienic practices. Cultural Politics of Hygiene in Bengal/India, 1890-1940 analyzes one such genealogy of hygiene in the context of late colonial Bengal. It argues that the meaning and role of hygiene in India were catalyzed on the crossroads of colonial governance, anticolonial struggles, cultural nationalism, and early 20th century social feminism. Affect, feeling, and sentiment were, however, no less important in the production of knowledge and practices of hygiene. Hygiene as a modern discourse, as shown in this book, not only produced emotions, sentiments, and feelings but was also constituted through them"--